The relationship of digital transformational leadership on employee performance with the mediation effect of knowledge management and innovation work behavior in retail company - Sri Hartati Kartoyo; Ardi Ardi; Margaretha Pink Berlianto (Enrichment : Journal of Management, 2023)
In this research, which was carried out at a Jakarta retail establishment with 192 staff-level respondents, we used Smart PLS V4 to investigate the relationships between digital transformational leadership (DTL), knowledge management (KM), innovation work behavior (IWB), and employee performance (EP). The following is a selection of the significant connections that our research has uncovered: DTL has a significant influence (=0.826, p = 0.001) on KM, which in turn has a positive influence (=0.427, p = 0.001) on both IWB and EP (=0.390, p = 0.001). The direct effects of DTL on IWB (= 0.310, p = 0.001) and EP (= 0.105, p = 0.014) are statistically significant; however, in the absence of KM, these effects are slightly attenuated. There is a statistically significant relationship between KM and IWB (= 0.518, p 0.001) and EP (= 0.473, p 0.001), respectively. The findings of this study are summed up by focusing on the significance of digital transformational leadership, knowledge management, and innovative work behavior in the context of improving employee performance in the retail industry. The findings of this study provide valuable insights to retail companies not only in Jakarta but also elsewhere. These findings highlight the necessity of investing in leadership development, knowledge management practices, and innovation strategies to foster higher employee performance and competitive advantage in the digital age